Comunidade e conflitualidades : a atuação da Polícia Militar em bairros periféricos de Cuiabá (MT) - Hayashi, Randalle Silva (2024)
This study aimed to analyze the phenomenon of institutional racism present in the police approach to young black residents of the neighborhoods Três Barras, Jardim Vitória, and Pedregal in Cuiabá (MT). Institutional racism is defined as the provision of public services in a discriminatory manner based on color, culture, or ethnic origin, violating constitutional principles. The research adopted a qualitative approach, with an exploratory phase followed by the description of reports of police violence. A literature review served as the basis, exploring topics such as racism, police violence, cities, politics, society, and economy. In addition, a document analysis was conducted, covering complaints of police violence reported to the Public Prosecutor's Office, the Public Defender's Office, and Police Ombudsmen and Internal during the period from 2020 to 2022. The results indicated the existence and persistence of institutional racism in interactions between the police and the young black individuals from the studied communities. These findings highlight the urgency of addressing this systemic issue to promote justice and social equality, with a police force that is more civic-minded and sensitive to racial issues.